Improvement of students’ physical fitness in physical education classes using CrossFit means - Oleksandr Pryimakov; Stanislav Prysiazhniuk; Georgiy Korobeynikov; Dmytro Oleniev; Vitalii Polyvaniuk; Nataliya Mazurok; Olena Omelchuk (Physical Education of Students)
Background and Study Aim. The purpose of the study is to develop and experimentally substantiate the efficiency of methods to improve the physical fitness (PF) of students in physical education classes using CrossFit means.